2023
DOI: 10.1088/1361-6641/acec65
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam irradiation effects on GaN/InGaN multiple quantum well structures

Liyuan Yu,
Jianhua Hu,
Yuchen Ma
et al.

Abstract: GaN-based semiconductors have a strong potential for applications in space systems because of their high radiation resistance. Here, we investigate the influence of 1.5 MeV electron irradiation on the structural, electrical, and optical properties of InGaN/GaN multiple quantum wells (MQWs). The results show that at lower electron fluencies, the indium content in the
InGaN/GaN MQWs decreases by about 0.4% because of the ionization of valence electrons induced by electron irradiation, but at higher elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The mechanisms of Ga + ion implantation into III–V semiconductors have been established, 18 and it was found that Ga + implantation into InGaN may produce metallic In clusters during the Ga + ion irradiation, which can be attributed to the lower displacement energy of In than Ga 19 . Besides, the ionisation‐enhanced diffusion may also be significant 20 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of Ga + ion implantation into III–V semiconductors have been established, 18 and it was found that Ga + implantation into InGaN may produce metallic In clusters during the Ga + ion irradiation, which can be attributed to the lower displacement energy of In than Ga 19 . Besides, the ionisation‐enhanced diffusion may also be significant 20 …”
Section: Introductionmentioning
confidence: 99%